2021
DOI: 10.3390/ijms22136942
|View full text |Cite
|
Sign up to set email alerts
|

Stage-Specific Characterization of Physiological Response to Heat Stress in the Wheat Cultivar Norin 61

Abstract: Bread wheat (Triticum aestivum) is less adaptable to high temperatures than other major cereals. Previous studies of the effects of high temperature on wheat focused on the reproductive stage. There are few reports on yield after high temperatures at other growth stages. Understanding growth-stage-specific responses to heat stress will contribute to the development of tolerant lines suited to high temperatures at various stages. We exposed wheat cultivar “Norin 61” to high temperature at three growth stages: s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 42 publications
2
8
0
Order By: Relevance
“…The changes in metabolite concentrations described in the previous sections were correlated with the values of the agronomic traits obtained in our previous study ( Figure 6 , Tables S4 and S5 ) [ 12 ]. Matsunaga et al [ 12 ] divided agronomic traits into three clusters based on the response to high-temperature treatment: in agronomical cluster 1, traits were positively affected by heat during GS1; in agronomical cluster 2, traits were negatively affected by heat during all stages; and in agronomical cluster 3, traits were affected negatively by heat during GS1 but positively during GS3.…”
Section: Resultssupporting
confidence: 67%
See 4 more Smart Citations
“…The changes in metabolite concentrations described in the previous sections were correlated with the values of the agronomic traits obtained in our previous study ( Figure 6 , Tables S4 and S5 ) [ 12 ]. Matsunaga et al [ 12 ] divided agronomic traits into three clusters based on the response to high-temperature treatment: in agronomical cluster 1, traits were positively affected by heat during GS1; in agronomical cluster 2, traits were negatively affected by heat during all stages; and in agronomical cluster 3, traits were affected negatively by heat during GS1 but positively during GS3.…”
Section: Resultssupporting
confidence: 67%
“…Previous studies suggested that high temperature during certain growth stages affects the senescence rate during seed formation [ 12 ]. Therefore, to explore the metabolic changes during the seed formation period under each temperature condition ( Figure 1 ), we quantified the stably detected metabolites (amino acids, organic acids, nucleic acids, and hormones) in the most recent flag leaves at 7 days post-anthesis (DPA) ( Table S1 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations